Held to Ransom: CMV Treatment in South Africa - Fatima Laher; Gail Ashford; Angela Cescon; Claire Cullen; Erica Lazarus; Adrian Puren; Linda Visser (AOSIS, 2010)
Cytomegalovirus is a multi-systemic infection reactivated in the immunocompromised. Diagnosis and treatment are prohibitively costly in sub-Saharan Africa, and efforts need to be made for their price reduction to support the expanding highly active antiretroviral treatment programme in the region.